MANAGER'S MARKETING COMMUNICATION STRATEGY IN DEVELOPING RELIGIOUS TOURISM OBJECTS BAYT AL-QUR'AN AL-AKBAR PALEMBANG'S LARGEST TYPICAL WOOD CARVING IN THE WORLD - Minsah, Minsah (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2025)
This study examines the marketing communication strategy employed in developing Bayt Al-Qur’an Al-Akbar, a unique religious tourism attraction in Palembang renowned for its world’s largest and most exquisite wood-carved Qur’an. Using a descriptive qualitative approach, the research explores the application of the marketing communication mix—advertising, sales promotion, public relations, publications, and direct marketing—in enhancing visitor interest and engagement. Additionally, this study analyzes the role of key influencing factors, including government and private sector support, human resources, infrastructure, and budget constraints. The findings reveal that while Bayt Al-Qur’an Al-Akbar possesses significant potential as a religious tourism destination, challenges such as limited promotional efforts and insufficient collaboration with related sectors hinder its optimal development. To address these issues, the study recommends strengthening human resource capabilities, expanding digital marketing initiatives, and improving infrastructure and accessibility. By implementing a more comprehensive marketing communication strategy, Bayt Al-Qur’an Al-Akbar can further solidify its position as a prominent religious tourism landmark, attracting both domestic and international visitors.